Pengaruh Kurikulum Merdeka Terhadap Hasil Belajar Matematika Siswa SMA Negeri 4 Baubau - Armin, Rismayani; Saadia, Wa Ode Nur Halimatus; Iriana, Artati (Jurnal Akademik Pendidikan Matematika, 2024)
The aim of this research is to determine the influence of the Merdeka curriculum on the students’ mathematics learning outcomes of SMA Negeri 4 Baubau. This research used an ex post facto method. The population in this study were all students in class XI, even semester, SMA Negeri 4 Baubau, consisting of 9 classes. The sample for this research, namely class XI/FI .3, was taken using purposive sampling technique. The instruments used in this research were questionnaires and diagnostic tests in the form of essays. The research results showed that the influence of the curriculum using simple linear regression obtained a sig value. Amounting to 0.000 for a significance level value of 0.05 (5%). Thus, the significant value is 0.000 < 0.05, so H1 is accepted and H0 is rejected. So it can be concluded that there is a significant influence of the Merdeka Curriculum on the Mathematics Learning Outcomes of Class XI/F1.3 Students at SMA Negeri 4 Baubau.